Salt intake and body weight correlate with higher blood pressure in the very elderly population: The Sukagawa study. Issue 7 (26th June 2019) - Iida, Hidekazu; Kurita, Noriaki; Takahashi, Sei; Sasaki, Sho; Nishiwaki, Hiroki; Omae, Kenji; Yajima, Nobuyuki; Fukuma, Shingo; Hasegawa, Takeshi; Fukuhara, Shunichi
Abstract: As few epidemiological studies have investigated the effect of lifestyle factors on hypertension in the very elderly population, we conducted a cross‐sectional study to examine the association of estimated salt intake and body weight with blood pressure in the very elderly population. We enrolled 288 participants aged 75 years or older who were residents of Sukagawa City, Fukushima Prefecture, Japan, who attended the health checkup conducted in 2015. Salt intake was estimated from spot urine samples using the Tanaka method. The mean values for age, estimated salt intake, and body weight of all participants were 79.7 years, 9.1 g/d (standard deviation 2.4 g), and 54.3 kg (standard deviation 10.2 kg), respectively. General linear models showed that salt intake and body weight were associated with higher systolic blood pressure (SBP) levels (per standard deviation higher level, adjusted difference 4.13 mm Hg [95% confidence interval 1.69‐6.57] and 5.34 mm Hg [95% confidence interval 2.12‐8.56], respectively). Body weight was associated with higher diastolic blood pressure (DBP) levels (per standard deviation higher level, 2.74 mm Hg [95% confidence interval 0.58‐4.90]). However, salt intake was not associated with higher diastolic blood pressure levels (per standard deviation higher level, 1.15 mm Hg [95% confidence interval −0.49 to 2.79]). Our findings suggest that higher SBP is associated with both salt intake and body weight and that higher DBP is associated with body weight in the very elderly population. This study provides a rationale for lifestyle modifications to prevent hypertension as a population approach.